UPAYA PENCEGAHAN STUNTING DAN PENYAKIT DEGENERATIF MELALUI POLA MAKAN DAN GAYA HIDUP SEHAT - Budhi Utami, Budhi Utami; Utami, Budhi (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Literacy culture in Indonesia is a very interesting issue to discuss. Considering that literacy culture in Indonesia is still low, not yet entrenched, and not yet ingrained in society. In the midst of the rapid rise of popular culture, books have never been a top priority. In fact, it is easier for people to absorb the culture of speaking and listening, rather than reading and then putting it in written form. Indonesian society is still dominated by a culture of oral communication or speech culture. People tend to prefer watching cellphones with status updates and following television broadcasts rather than reading. In the Nutrition Science course which discusses the role of Posyandu in efforts to prevent stunting and degenerative diseases, students observe Posyandu activities for toddlers and the elderly (ILP) in Mojoroto Village, Mojoroto District, Kediri City, with the hope that students will be able to apply the material on the topic of the Impact of Malnutrition on human health and the elderly's efforts to maintain health. Healthy living is the hope and dream of every normal human being, not only statically healthy but also dynamically healthy. A healthy lifestyle is influenced by the type of food consumed as well as sports activities, communication skills and establishing friendly relationships for the elderly.  or physical fitness and physical fitness efforts are health efforts that utilize physical activity to improve health status. Physical activity or sport is part of the basic needs in daily life, especially improving the level of health, which according to our ancestors is part of our life. However, with improvements and developments in today's technological world, all activities make it easier, causing us to move less (low body movement) or often referred to as hypokinetic, such as using remote controls, computers, lifts, escalators, transportation and other sophisticated equipment without balance. with physical activity, which results in influencing the occurrence of hypokinetic symptoms which encourage the formation of clots in the bloodstream, thereby influencing the occurrence of degenerative diseases such as diabetes mellitus, hypertension, stroke in the elderly.